2012
DOI: 10.3109/00365548.2012.717710
|View full text |Cite
|
Sign up to set email alerts
|

Years of potential life lost due to HIV infection and associated factors based on national HIV surveillance data in Latvia, 1991–2010

Abstract: A considerable number of years of potential life have been lost in Latvia due to HIV. YPLL is significantly associated with ethnicity and mode of HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…As supported by Andarwatolanrain (2016) that the potential life lost in men is lower than women. However, Karnite et al (2013) reported the opposite way, she found that the average years of YPLL for men in Lativa is higher than women, even if no significant relationship.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…As supported by Andarwatolanrain (2016) that the potential life lost in men is lower than women. However, Karnite et al (2013) reported the opposite way, she found that the average years of YPLL for men in Lativa is higher than women, even if no significant relationship.…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, Karnite reported the average YPLL in Latvia for 28.8 years (Karnite et al, 2013;Rumisha et al, 2020). Andarwatolanrain also found that there is meaningful relation between diagnosis age and the average years of YPLL, the lower the diagnosis age the bigger the YPLL (Andarwatolanrain, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…2 Desde 2007, Porto Alegre apresenta elevação persistente das taxas de mortalidade de mulheres relacionada à aids, 3,4 situando-se entre as capitais com as maiores taxas, especialmente entre mulheres de 30 a 39 anos. 5 Apesar das evidências da elevada carga de doença relacionada à aids nas mulheres, 1 são poucos os estudos dedicados a investigar os anos potenciais de vida perdidos (APVPs) nesse segmento da população, [6][7][8][9] estudos propostos a investigar o número de anos que determinada população deixa de viver se morrer prematuramente, por determinada causa. 10 Um deles, realizado na Tanzânia, sobre causas da mortalidade precoce, evidenciou que a aids foi responsável pelo maior número de APVPs, inclusive com aumento desse indicador entre 2006 e 2015, e que mulheres tiveram mais APVPs por essa causa do que homens.…”
Section: Introductionunclassified